Islamic Education in Indonesia and Malaysia (The Existence and Implementation until 20 th century) - Margono, Untung (AT TADIB, 2012)
This study discusses the comparison between the existence and theimplementation of Islamic Education in Indonesia and Malaysia both fromreligious educational institutions and public educational institutions. The mainproblem focuses on: what are the issues that covered equality and differencesbased on the existence and implementation, and also what matters are dominantlyand substantially considered as supporting factors for the cause of those twopoints (existence and implementation). The study describes the policy from thetwo countries toward Islamic Education including their goals and objectives.In addition, this study is also exploring the development of Islamic Educationin the two countries based on the historical facts and current situation. Eventually,the analysis of comparison emphasized on the existing facts and reality.